The junk trade from Southeast Asia : - Fusetsu-gaki, Tôsen (Institute of Southeast Asian Studies, 1998)
This book offers straightforward ... excellent translations of a rare set of Japanese records with limited, although helpful, explanations and notes dealing mainly with matters of Southeast Asian interest